Hydrodynamic optimization of a Sweptback Stern Foil for resistance reduction in flat-hull ships: A CFD-based extension of the Hull Vane concept - Nabawi, Rahmat Azis; Syahri, Budi; Alfana, Yogi Dian; Fernandez, Donny (Teknomekanik, 2026)
Flat-hull ships are known to have higher resistance than streamlined hulls. Although the Hull Vane® concept has been proven effective as a stern-mounted energy-saving device through pressure-field modification and stern-wave interaction, most previous studies have focused on straight-foil configurations (straight planform). The effect of planform shape optimization, particularly the sweptback configuration, on the hydrodynamic performance of flat-hull ships is limited in the literature. This study modifies the geometry of a Hull Vane® into a sweptback stern foil and evaluates its performance using Computational Fluid Dynamics simulations. The results show that a 15° sweptback angle yields the greatest reduction in total drag. Velocity contour analysis shows a narrower wake and a more uniform velocity-gradient distribution in the stern area for the 15° swept-back stern-foil configuration compared to other configurations. Meanwhile, the turbulence length distribution shows a tendency toward reduced intensity of large-scale turbulent structures behind the ship, indicating improved wake-flow characteristics. The identified drag reduction mechanism primarily stems from improved pressure recovery and modified pressure distribution in the stern area, which is consistent with the working principle of Hull Vane®. Optimizing the sweptback planform geometry yields more efficient flow interaction than the straight-foil configuration. These findings indicate that planform optimization is an important design parameter in the development of stern foils to improve the hydrodynamic efficiency of medium-to high-speed commercial vessels.